Profile of Hepatocellular Carcinoma: An Experience from a Tertiary Care Hospital - Laiba Naseer, Sharoon Sabir, M. Kashif Azeem, Shahidah Zaman, Asad Ullah Mahmood, Maryam Mastoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hepatocellular carcinoma (HCC) is the primary liver cancer around the world, and it has now become the third leading cause of cancer-related mortality. With an increasing global incidence, HCC is becoming a major health burden. The incidence of HCC varies from 0.3% to 1.6% in Asian countries. The present study aimed to assess the clinical and etiological profile of hepatocellular carcinoma in a tertiary care hospital. Methodology: This retrospective study was conducted on 124 hepatocellular carcinoma patients in the Department of Gastroenterology, Jinnah Hospital, Lahore from June 2019 to May 2022. All the patients of age 10 years to 75 years fulfilling the diagnostic criteria were enrolled in this study. Patient’s cytohistological, clinical, radiological, and etiological data were recorded and analyzed. Individual relevant features were noted in pre-designed proforma. SPSS version 25 was used for data analysis. Results: Of the total 124 HCC patients, there were 78 (62.9%) male and 46 (37.1%) females. The overall mean age was 48.63±6.78 years. Liver cirrhosis was present in 91 (73.4%) patients out of which 14 (15.4%) were asymptomatic. The prevalent signs of hepatic decompensation were ascites 67 (54%) and Jaundice 23 (18.5%). Based on etiological data, the prevalence of the cryptogenic, Hepatitis B, and C were 58 (46.8%), 20 (16.1%), and 6 (4.8%) respectively. Tumor thrombosis was found in 18 (14.5%). Based on biopsy specimens, HCC with steatosis were seen in 19 (15.3%) patients. During surveillance, about 32 (25.8%) cirrhotic HCC patients were diagnosed. Conclusion: The present study found that the most prevalent etiology was hepatocellular carcinoma. Most patients were asymptomatic and had major complaints of abdominal pain with certain specific comorbidities. Hypertension, diabetes, and ischemic heart disease were the specific co-morbidities in hepatocellular carcinoma patients. In our population, the prevalent cause of HCC was Hepatitis B. Keywords: Clinical profile, Etiology, Hepatocellular Carcinoma